The contribution of the endogenous TRPV1 ligands 9‐HODE and 13‐HODE to nociceptive processing and their role in peripheral inflammatory pain mechanisms. (25th March 2013) - Alsalem, Mohammad; Wong, Amy; Millns, Paul; Arya, Pallavi Huma; Chan, Michael Siang Liang; Bennett, Andrew; Barrett, David A; Chapman, Victoria; Kendall, David A
<x xml:space="preserve">Abstract</x> Background and Purpose The transient receptor potential vanilloid type 1 (TRPV1) plays a fundamental role in the detection of heat and inflammatory pain responses. Here we investigated the contribution of two potential endogenous ligands [9‐ and 13‐ hydroxyoctadecadienoic acid (HODE)] to TRPV1‐mediated noxious responses and inflammatory pain responses. Experimental Approach 9‐ and 13‐HODE, and their precursor, linoleic acid, were measured in dorsal root ganglion (DRG) neurons and in the hindpaws of control and carrageenan‐inflamed rats by liquid chromatography/tandem electrospray mass spectrometry. Calcium imaging studies of DRG neurons were employed to determine the role of TRPV1 in mediating linoleic acid, 9‐HODE‐ and 13‐HODE‐evoked responses, and the contribution of 15‐lipoxygenase to the generation of the HODEs. Behavioural studies investigated the contribution of 9‐ and 13‐HODE and 15‐lipoxygenase to inflammatory pain behaviour. Key Results 9‐HODE (35 ± 7 pmol g−1) and 13‐HODE (32 ± 6 pmol g−1) were detected in hindpaw tissue, but were below the limits of detection in DRGs. Following exposure to linoleic acid, 9‐ and 13‐HODE were detected in DRGs and TRPV1 antagonist‐sensitive calcium responses evoked, which were blocked by the 15‐lipoxygenase inhibitor PD146176 and an anti‐13‐HODE antibody. Levels of linoleic acid were significantly increased in the carrageenan‐inflamed hindpaw (P < 0.05), whereas levels of 9‐ and 13‐HODE were, however, decreased. Intraplantar co‐administration of anti‐9‐ and 13‐HODE antibodies and treatment with PD146176 significantly (P < 0.01) attenuated carrageenan‐induced hyperalgesia. Conclusions and Implications This study demonstrates that, although 9‐ and 13‐HODE can activate TRPV1 in DRG cell bodies, the evidence for a role of these lipids as endogenous peripheral TRPV1 ligands in a model of inflammatory pain is at best equivocal.